PLATFORMS AND METHODS FOR OPTIMIZING HOST ANTIGEN PRESENTATION AND HOST ANTITUMOR AND ANTIPATHOGEN IMMUNITY - CHERPES, Thomas L; VICETTI MIGUEL, Rodolfo Daniel; QUISPE CALLA, Nirk E (2020)
Disclosed herein are methods and platforms for increasing utility and efficacy of a cellular vaccine. Specifically, disclosed are steps that optimize ex vivo B cell expansion and boost host in vivo immunity. Also disclosed is a platform for enhancing effectiveness of antigen presentation and antigen-specific immune responses. Also disclosed is a method for enhancing effectiveness of APCs in a subject. Also disclosed are vaccines and kits based on the platform.